Adapting to climate change among transitioning Maasai pastoralists in southern Kenya: an intersectional analysis of differentiated abilities to benefit from diversification processes. Issue 1 (2nd January 2023) - Marty, Edwige; Bullock, Renee; Cashmore, Matthew; Crane, Todd; Eriksen, Siri
ABSTRACT: With increasingly fragmented rangelands, restricted mobility and climatic stress, diversification has accelerated among East African pastoralists. Diversification is also promoted as a climate change adaptation strategy to reduce climatic exposure. Through a study of a Maasai communal land in southern Kenya, we analyze how pastoralists navigate changing access to key productive resources that are linked to diversification processes, social differentiation, and the reshaping of livelihood practices. By integrating an intersectional approach in access theory, we unpack a deeper level of context specific patterns of inclusion and exclusion embedded within evolving production relations.